تأثير التحرر المصرفي الائتماني في مؤشر الربحية المصرفية: بحث تطبيقي لعينة من المصارف التجارية الخاصة المدرجة في سوق العراق للاوراق المالية (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:               The impact of banking credit liberalization on the banking profitability Indicator/ Applied research on a sample of private commercial banks listed on the Iraq Stock Exchange.The aim of the research is to shed light on an important and vital topic that is considered one of the components of sound financial reform, which is credit banking liberalization, and to explain its impact on the banking profitability Indicator, which in turn will be supportive of economic growth in the country, as economic reform does not occur except by paying attention to the banking sector, which is manifested through Banking liberalization, which was adopted in Iraq after 2003, is a result of the multiple changes and developments taking place in the environment. Therefore, the banking liberalization policy is part of the banking developments that are based on liberating banking services from the administrative restrictions imposed on banks by changing the lending behavior of banks, where borrowers are evaluated based on their ability. and their credit qualifications and not on state decisions, The research problem was defined by raising the question (to what extent does credit banking liberalization contribute to the profitability Indicator of the banks studied?), and the research adopted the descriptive, analytical and standard approach to financial data for the years (2013-2022), and was applied to a sample of private commercial banks listed in the Iraqi market. For securities represented by (Bank of Baghdad, National Bank of Iraq, Assyria International Bank for Investment, International Development Bank for Investment and Finance), and the data was analyzed using the statistical program SPSS V.18. The (private credit rate) Indicator was calculated to measure banking credit liberalization, and the (rate of return on assets) and (rate of return on equity) Indicator were adopted to measure banking profitability. The research concluded that there is fluctuation between rise and fall in credit ratios. Which had an impact on the banking profitability Indicator in the banks studied, due to the economic conditions in the country during the years of research